Isolated reversible involvement of bilateral internal capsule on magnetic resonance imaging in case of acute hypoglycemic encephalopathy: A case report (Indian Journal of Case Reports, 2024)
Hypoglycemic encephalopathy (HE) is a metabolic disorder that can lead to morbid manifestations including motor deficits, transient memory loss, persistent vegetative state, and even deep coma. Due to potential clinical symptom overlap with acute stroke, accurate diagnosis is very crucial. Besides the patient’s medical history and routine blood investigations, magnetic resonance imaging (MRI), particularly diffusion-weighted imaging (DWI), plays a valuable role in diagnosing HE. We present a case of acute hypoglycemia with reversible changes in the bilateral internal capsule seen on DWI-MRI.